THE DIFFERENCE OF BEHAVIOR AND MANGO FARMERS’ INCOME IN IMPLEMENTING OFF SEASON AND ON SEASON FARMING - Esa Noerbayinda; Eliana Wulandari (AGROLAND The Agricultural Sciences Journal (e-Journal), 2021)
The production of gedong gincu mango tends to be abundant lead to the selling price could decrease. Mango farmers in Jatibarang Sub-district had implemented off season farming as a solution to maintain the availability of mango production throughout the year which would have implications on the rising selling price. The behavior of farmers in on and off season could be different that may affect the cost, sale price and income of farmers. This study aims to analyze the differences behavior gedong gincu mango farmers in on and off season as well as its effect on their income. This research was conducted using survey method. The data analysis used a descriptive statistic, Mann Whitney tests and income analysis. The results showed no difference in farmers’ behavior in terms of fertilization and pruning frequency. Farmers in Jatibarang Sub-district as a whole have implemented off season farming so that there are differences in behavior in terms of the spraying frequency and applying paclobutrazol. Off season farming was more profitable than on season farming, with the average selling price reached IDR 25,200 per kg and average income of IDR 52,680,594. Therefore, off season farming could be an option to increase farmers’ income